Subjective Models of the Macroeconomy: Evidence from Experts and a Representative Sample - Peter Andre; Carlo Pizzinelli; Christopher Roth; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
Using a sample of 2,200 households representative of the US population and a sample of more than 1,000 experts, we measure beliefs about how aggregate unemployment and in ation respond to different macroeconomic shocks. Expert predictions are quantitatively close to standard DSGE models and VAR evidence. While households' beliefs are directionally aligned with those of experts in the case of oil supply shocks and government spending shocks, they predict an opposite reaction of in ation to monetary policy and income tax shocks. A substantial fraction of deviations of household predictions can be explained by the use of a simple affective heuristic.
Keywords: D83; D84; E31; E52; E71; 330; Expectation Formation; Subjective Models; Heuristics; Macroeconomic Shocks; Monetary Policy; Fiscal Policy